Edukasi Kesehatan tentang Pemanfaatan Daun Durian Secara Tradisional untuk Mengatasi Nyeri Sendi, Peradangan Ringan, dan Pembengkakan pada Lansia: Health Education on the Traditional Use of Durian Leaves for Managing Joint Pain, Mild Inflammation, and Swelling among Older Adults - Putri, Yurizka; Wahyuny, Romy; Sianturi, Rismalia Br; Sari, Devi Novita; Oktavia, Dilla (Jurnal Abdi Keperawatan dan Kedokteran, 2026)
Joint pain, mild inflammation, and swelling are common health complaints among older adults and often interfere with daily activities and quality of life. In rural communities, older adults frequently rely on medical drugs without adequate knowledge of complementary traditional therapies. Durian (Durio zibethinus) leaves are locally available and traditionally believed to have anti-inflammatory properties; however, limited knowledge regarding their benefits, preparation, and safe use restricts their optimal utilization among older adults. This community service program employed a pre–post test design with a one-group approach. The participants consisted of 10 older adults aged 60 years and above living in Rambah Tengah Utara Village. The intervention was a health education session focusing on the benefits, preparation methods, and safe traditional use of durian leaves to manage mild inflammation and joint pain. Educational methods included lectures, discussions, and the use of leaflets and posters. Data on participants' knowledge were collected before and after the intervention using a structured questionnaire. Data analysis was conducted descriptively and supported by statistical comparison of pre- and post-intervention scores using Wilcoxon signed-rank test. The results showed a significant improvement in participants' knowledge after the health education intervention. The mean pre-test score was 4.8 ± 1.3, which increased to 8.7 ± 0.9 in the post-test (p < 0.001). All participants (100%) demonstrated increased understanding of the benefits of durian leaves, appropriate preparation techniques, and limitations of their use as complementary therapy for joint pain and mild inflammation. Health education on the traditional use of durian leaves effectively improves older adults' knowledge regarding complementary management of joint pain and mild inflammation. Community-based educational interventions utilizing local resources are recommended to support health promotion and improve the quality of life of older adults.